The Influence of Trust in the Government on Tax Compliance with the Perception of Tax Fairness as A Mediating Variable - Hayati, Nururl; Syahdan, Saifhul Anuar; Fahrianta, Riswan Yudhi; Boedi, Soelistijono (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study aims to examine the influence of trust in the government on tax compliance with perceptions of tax fairness as a mediating variable. The research used a quantitative method. The data used are primary, obtained directly from respondents’ responses to the distributed questionnaires. The population in this study consists of MSME taxpayers in the Food and Beverage sector in the City of Banjarmasin. The sampling technique employed is non-probability sampling, specifically convenience sampling. The research sample consists of 100 taxpayers. The results indicate that trust in the government has a positive effect on perceptions of tax fairness and tax compliance; perceptions of tax fairness have a positive impact on tax compliance; and perceptions of tax fairness mediate the relationship between trust in the government and tax compliance